Prevalence of MASLD and fibrosis in Turkey: Results from a multicenter study of at-risk populations - Gediz Dogay Us; Francesco Innocenti; Ozgur Muhammet Koc; Volkan Demirhan Yumuk; Zeynep Banu Gungor; Ger H. Koek (PLoS ONE, 2026)
Background Turkey represents a high-risk setting for metabolic dysfunction-associated steatotic liver disease (MASLD), with national obesity and diabetes rates of 32% and 15%, respectively. Yet, no prior studies have systematically assessed MASLD and fibrosis prevalence and the independent contribution of these metabolic risk factors in at-risk Turkish populations exhibiting cardiometabolic risks. Methods 1,039 adults were enrolled in a multicenter cross-sectional study conducted between 2022 and 2024. All participants presented with at least one of the current MASLD diagnostic criteria. Standardized clinical assessments were performed. Individuals with excessive alcohol consumption (<30 grams/day for men and <20 grams/day for women) were excluded. Steatosis and fibrosis were evaluated using controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) via vibration-controlled transient elastography. MASLD was defined as CAP ≥ 248 dB/m, and significant fibrosis as LSM ≥ 8 kPa. Multivariable logistic regression analyses were used to identify factors associated with MASLD and fibrosis. Results The mean age of the study population was 51.7 ± 13.1 years, and 49.4% were male. The mean body mass index was 30.54 ± 5.85 kg/m 2 . Obesity and central obesity were seen in 48.5% and 75.1% of the subjects, respectively. MASLD, significant fibrosis (>F2) and advanced fibrosis (>F3) prevalence were 57.5% (95% CI: 54.4%–60.4%), 7.6% (95% CI: 6.1%–9.4%) and 2.6% (95% CI: 1.8%–3.8%) respectively. Multivariable logistic regression of MASLD revealed a significant association with female sex (OR=0. 548; 95% CI: 0.391, 0.770), obesity (OR=2.208; 95% CI: 1.535, 3.177), insulin resistance (OR=2.09; 95% CI: 1.528, 2.881), metabolic syndrome (OR=2.436; 95% CI: 1.614, 3.679) and central obesity (OR=2.816; 95% CI: 1.725, 4.595). Multivariable logistic regression of fibrosis demonstrated a significant association with high income (OR=0.256; 95% CI: 0.069, 0.948), obesity (OR=4.845; 95% CI: 2.540, 9.242), diabetes, (OR=2.172; 95% CI: 1.306, 3.610), insulin resistance OR=4.205; 95% CI: 2.144, 8.246) and metabolic syndrome (OR=2.053; 95% CI: 1.042, 4.045). Conclusion MASLD is prevalent in more than half of the at-risk population studied. Male sex, obesity, metabolic syndrome, insulin resistance and central obesity are significant risk factors associated with it. Despite the high MASLD prevalence, significant fibrosis is less prevalent and is associated with obesity, metabolic syndrome, insulin resistance and diabetes. Further research is warranted in this population. Study Registration ClinicalTrials.gov, ID: NCT05194553 .